Scientific Collaboration and Development of Scientific Community – Contribution to Research of Development of Information Science in Croatia - Pečarić, Đilda (Array, 2010)
Field of information science in Croatia includes seven disciplines: archivistics and documentation, communicology, information science, information systems, lexicography, librarianship and museology. Until now, research about scientific collaborations and correlations on individual, institutional, national or international level within these disciplines does not exist in Croatia. This research shows scientific collaborations among disciplines in the field of information science using bibliometrics methods, by indicators about collaboration, in order to establish reciprocity of scientists and their influence and connections. On the corpus of 22, 210 cited bibliographic units retrieved from doctoral dissertations in information science, scientific collaboration and influence of authors’ productions and co-authors connections to the development of scientific community in the field of information science in Croatia is shown. Scientific collaboration is followed through three indicators: a) the distribution of citations according to disciplines and periods in order to identify the factor of connections and coherence among certain disciplines ; b) by the analysis of the number of co-authors, more precisely, by the analysis of co-authors’ connections, level and form of scientific collaboration inside certain scientific disciplines as well as overall field of information science is followed ; c) by the analysis of most cited authors in conceptual knowledge zone, the dynamics of the development of scientific paradigm and their dominant authors in thirty year researched period in is shown, both according to periods and according to disciplines.